Persepsi dan Preferensi terhadap Vertical Greenery Berdasarkan SBE di Kota Pekanbaru - Mutmaini, Leny Faridhotul; Budiarti, Tati; Nasrullah, Nizar (Jurnal Lanskap Indonesia, 2024)
Vertical greenery in the city of Pekanbaru is very difficult to find because there are still many people who do not know the various benefits and uses of vertical greenery with limited land. This study focuses on the city of Pekanbaru at 10 locations found. The research location is in the District Limapuluh, District Pekanbaru City, District Marpoyan Damai with 2 location points. Area Sukajadi and in the District Bukit Raya each with 3 location points. This paper aims to examine perceptions, preferences, color freshness and plant density analyzed by SBE. Vertical greenery is generally found in cafes, hotels and included in the Pekanbaru Park service. The vertical greenery owned by the company in management is more maintained and aesthetically so that it gets the highest score. Meanwhile, the Pekanbaru office tends to be simple in design and many are neglected. The results showed that the people of Pekanbaru city were still unfamiliar with the existence of vertical greening. While the results of the evaluation of the aesthetic value show that the average vertical greenery in Pekanbaru City has a good aesthetic value at a moderate level. Both in terms of design, freshness of color and density level are influenced by several aspects such as structure, environment, activity intensity, type of plant vegetation and maintenance.